Performance of some rice (Oryza sativa L.) cultivars under water shortage and high temperature stress - A.A.E., Mohamed; Fiaz, Sajid; Wang, Xiukang; Ali, Mohsin; Parveen, Noshi; M. Gaballah, Mahmood; Ali, Sardar; Abdallah, Abdallah A.; Ahmed, Salwa I. (Penerbit Universiti Kebangsaan Malaysia, 2021)
Water shortage and heat are the most devastating abiotic stresses threating global food security. To understand the behavior of germplasm under both abiotic stresses, thirteen rice genotypes were selected for the study to make evaluation under water shortage and heat stress condition. The results showed that the year mean squares were significant and highly significant for all agronomical traits except, flag leaf area, number of tillers plant-1, number of panicles plant-1, 100 grain weight, grain yield plant-1 and harvest index indicated overall wide differences of weather during both years. Environments mean squares were found to be highly significant over all traits were used, indicating that all environments showed significant differences. The highly significant differences were observed among genotypes and G x E interaction for all characteristics except, panicle length. Concerning the cultivars performance across three environments, the cultivars Giza 178, Giza 179, Sakha 107, Hybrid 1, Hybrid 2 gave the best desirable values over normal, drought and heat stress conditions so, these cultivars are considered to play vital role in breeding program to enhancement for drought and heat stresses and have high yield potential. The highly significant and positive correlation were found among the all traits under investigation except with flag leaf angle, leaf rolling and sterility percentage. The results will further help to utilize the genotypes for further crop improvement breeding programs.